A Generic Data Privacy Approach for Relational Databases and Data Warehouses - Rahul Kumar Sharma (International Journal of Intelligent Systems and Applications in Engineering, 2023)
Currently data privacy is a big challenge for relational databases and data warehouses. Data privacy concerns are extremely critical in today’s data driven world due to data privacy regulations like Global Data Protection Legislation (GDPR). Data privacy in relational databases and data warehouses is typically implemented using row and column level security. Currently most of the databases and data warehouses do not support row and column level security and very few of the databases and data warehouses support it in a very customized or specific way. This paper discusses an approach that can be used to achieve data privacy for relational databases and data warehouses in a generic and integrated way. A generic and integrated data privacy layer is proposed in this paper. This generic and integrated data privacy layer will provide row and column level security using rules and policies that can be defined at user, group or role level and will work with relational databases and data warehouses.